(3ZGjI GdhUhd hEjVGM GdSHd aj TQM eNJUQ efJgi GdSDGd hGdCeds - (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s; (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, CHh YeQh LeGd GdOjf GHf GdMGLH,J (B646 (3g` s ((3eMeO Hf WGgQ GdSeGhi s)
(3ChdgG (B:s
(3CeG HYO abO GWHbJ GdYbdGA hGJabJ GdYdeGA s
(3BNQgG (B:s
(3ai GdeQcHGJ hai GdMOhO JQLjMGJ cKjQI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs